Empirical Modeling for a Submerged ARC Welding Process for Predicting the Weld Bead Geometry and Microstructure - Kumar, Parveen (My University, 2009)
The present study has been done to study the effect of different input parameters on the desired responses in the submerged arc welding process. Partial factorial technique has been used for the design of experiments. The effects of flux, current, travel speed and voltage have been evaluated on the bead height, bead width, depth of penetration, micro hardness and microstructure of the heat affected zone. The effect of all the input parameters on the output responses have been analyzed using the analysis of variance (ANOVA) and empirical modeling. The effect of variation in input parameters has been studied on the microstructure of the heat affected zone. Plots of significant factors, S/N ratio and empirical modeling have been used to determine the best-fit relationship between the response and the model parameters.
Keywords: Submerged Arc Welding; Optimization and Microstructure